2016
DOI: 10.1016/j.joca.2016.01.982
|View full text |Cite
|
Sign up to set email alerts
|

Value of tomosynthesis for lesion evaluation of small joints in osteoarthritic hands using the OARSI score

Abstract: In conclusion, tomosynthesis depicts more osteoarthritic changes in the small joints of the hand than conventional radiography using the OARSI scoring system and CT as the standard of reference.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Therefore, DTS may offer higher sensitivity and lower cost while combining the advantages of CT and CR. Due to these advantages of DTS, some studies have used DTS to assess osteoarthritis and rheumatoid arthritis of the hand (Duryea et al, 2003;Canella et al, 2011;Martini et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, DTS may offer higher sensitivity and lower cost while combining the advantages of CT and CR. Due to these advantages of DTS, some studies have used DTS to assess osteoarthritis and rheumatoid arthritis of the hand (Duryea et al, 2003;Canella et al, 2011;Martini et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Specialized training is also required, which limits the number of qualified readers. Recently, several authors have reported that tomosynthesis represents more joints with JSN than radiography in RA or osteoarthritis patients [7,8], with a small increase from 0.13 to 0.25 mGy in mean total radiation dose [5]. These results may be explained by less overlapping anatomy on tomosynthesis images in contrast to the projection radiographs [4,30].…”
Section: Discussionmentioning
confidence: 99%
“…As for joint space narrowing (JSN), tomosynthesis has been reported to facilitate accurate evaluation of joint space width better than radiography, even with oblique incidence of the X-ray beam [7]. In addition, Martini et al have shown that tomosynthesis depicts JSN with higher sensitivity than radiography in cadaveric hands with osteoarthritis [8].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Recently, cone-beam computed tomography (CT) and tomosynthesis were introduced for further clinical applications. [3][4][5] Here, we report the initial findings on imaging performance of a prototype version of three-dimensional (3-D) cone-beam CT imaging implemented on a twin robotic x-ray system (Multitom Rax, Siemens Healthcare GmbH, Erlangen, Germany). It is a multifunctional unit that is able to perform conventional x-rays and fluoroscopic examinations from different angles due to a specialized robotic mechanism.…”
Section: Introductionmentioning
confidence: 99%